Hubungan Dukungan Keluarga Dengan Fungsi Kognitif Pada Lansia Diabetes Mellitus Di Wilayah Kerja Puskesmas Purwosari - Wardani, Siska Amalia, Arina Maliya, S.Kep., Ns.,M.Si., Med (2017)
In people at the age of 70 years upwards a person susceptible to the disease one of them diabetes mellitus, other than that the elderly also experienced a decrease in cognitive function so unable to perform daily activities that require the help of others to take care of themselves. Based on this, family support is needed to treat elderly more intensively, especially in elderly with diabetes mellitus. The purpose of this study was to determine the relationship between family support and cognitive function in elderly diabetes mellitus. The research type is quantitative, descriptive correlative research design, cross sectional approach. Population in this research is elderly patient of diabetes mellitus in Work Area Purwosari Public Health Center Surakarta as many as 102 elderly patient of diabetes mellitus. Determination of sample data using slovin formula and sampling technique non probability sampling with snowball sampling. Measuring tool with questionnaire and MMSE (Mini-Mental State Exam). Analysis of data with univariate and bivariate with chi square. The result of this study is elderly diabetes mellitus of puskesmas Purwosari majority area have good family support, elderly diabetes mellitus area of puskesmas Purwosari majority have normal cognitive function. There is a relationship of family support with cognitive function in elderly diabetes mellitus of puskesmas Purwosari p value 0.0001 <0,05 The conclusion of this study is there is a relationship of family support with cognitive function in elderly diabetes mellitus Purwosari puskesmas area. The results of the study into information about the importance of family support is very important for the elderly with diabetes mellitus.